2018
DOI: 10.1074/jbc.m117.813931
|View full text |Cite
|
Sign up to set email alerts
|

The actin-organizing formin protein Fhod3 is required for postnatal development and functional maintenance of the adult heart in mice

Abstract: Cardiac development and function require actin-myosin interactions in the sarcomere, a highly organized contractile structure. Sarcomere assembly mediated by formin homology 2 domain-containing 3 (Fhod3), a member of formins that directs formation of straight actin filaments, is essential for embryonic cardiogenesis. However, the role of Fhod3 in the neonatal and adult stages has remained unknown. Here, we generated floxed mice to bypass the embryonic lethality of an knockout (KO). Perinatal KO of in the heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 47 publications
(69 reference statements)
3
30
0
Order By: Relevance
“…The adult heart of Fhod1 KO mice showed apparently normal sarcomeric structures composed of the Z-line (marked with the antibody to α-actinin) and thin actin filaments (stained with phalloidin; Figure 4a). This is in striking contrast to Fhod3 depletion, which causes disruption of sarcomeres (Kan-o et al, 2012;Ushijima et al, 2018). Furthermore, we paid special attention to the intercalated discs, specialized cell-cell contacts in the heart, since Fhod1 has been reported to be accumulated at intercalated discs (Al Haj et al, 2015;Dwyer et al, 2014).…”
Section: Effect Of Fhod1 Gene Disruption In the Cardiac Sarcomerementioning
confidence: 94%
See 3 more Smart Citations
“…The adult heart of Fhod1 KO mice showed apparently normal sarcomeric structures composed of the Z-line (marked with the antibody to α-actinin) and thin actin filaments (stained with phalloidin; Figure 4a). This is in striking contrast to Fhod3 depletion, which causes disruption of sarcomeres (Kan-o et al, 2012;Ushijima et al, 2018). Furthermore, we paid special attention to the intercalated discs, specialized cell-cell contacts in the heart, since Fhod1 has been reported to be accumulated at intercalated discs (Al Haj et al, 2015;Dwyer et al, 2014).…”
Section: Effect Of Fhod1 Gene Disruption In the Cardiac Sarcomerementioning
confidence: 94%
“…Fhod3 is highly expressed in the heart and also in the kidney and brain, but to a lesser extent (Kanaya et al, ). In line with this expression pattern, Fhod3 plays an essential role in assembly of actin into myofibrils in cardiomyocytes (Iskratsch et al, ; Taniguchi et al, ), which was subsequently verified at the whole heart level by the analysis of conventional and conditional Fhod3‐knockouot mice (Kan‐o et al, ; Ushijima et al, ). The critical roles of Fhod3 in regulation of actin assembly in the heart is further supported by the clinical observations that genetic variants of Fhod3 are associated with hypertrophic and dilated cardiomyopathies (Arimura et al, ; Wooten et al, ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…FHOD3, a member of the diaphanous‐related formins (DRF), is implicated in the regulation of actin assembly in cardiomyocytes and in sarcomere organisation during myofibrillogenesis . Studies in FHOD3 ‐knockout mice established that FHOD3 plays a role in the maintenance of normal cardiac function of the perinatal and adult heart . In 2018, Ochoa et al first reported that FHOD3 was considered a novel genetic cause of HCM in a large scale European population study.…”
Section: Discussionmentioning
confidence: 99%